Service Excellent Rumah Sakit Amalia dan HVA Pare Kediri - Sinollah Sinollah (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
This study aims to analyze the influence of excellent service variables consisting of ability, attitude, appearance, attention, action, responsibility, accuracy and comfort to patient satisfaction at Amelia and HVA Pare Hospital. To answer that goal, this research uses quantitative research using survey methods. Sampling using the Malhotra formula that is five times the number of variables by 40 respondents per hospital. Data collection techniques used were questionnaires, interviews, and documentation. Data analysis uses multiple linear regression analysis. From the analysis it can be seen that the excellent service quality variables consisting of ability, attitude, appearance, attention, action, responsibility, accuracy and comfort affect customer satisfaction at Amelia and HVA Pare Hospital. Of the eight dominant variables that influence is Comfort.